SQSTM1/p62 mediates crosstalk between autophagy and the UPS in DNA repair. Issue 10 (2nd October 2016) - Hewitt, Graeme; Carroll, Bernadette; Sarallah, Rezazadeh; Correia-Melo, Clara; Ogrodnik, Mikołaj; Nelson, Glyn; Otten, Elsje G.; Manni, Diego; Antrobus, Robin; Morgan, Brian A.; von Zglinicki, Thomas; Jurk, Diana; et al.
ABSTRACT: SQSTM1/p62 (sequestosome 1) selectively targets polyubiquitinated proteins for degradation via macroautophagy and the proteasome. Additionally, SQSTM1 shuttles between the cytoplasmic and nuclear compartments, although its role in the nucleus is relatively unknown. Here, we report that SQSTM1 dynamically associates with DNA damage foci (DDF) and regulates DNA repair. Upon induction of DNA damage SQSTM1 interacts with FLNA (filamin A), which has previously been shown to recruit DNA repair protein RAD51 (RAD51 recombinase) to double-strand breaks and facilitate homologous recombination (HR). SQSTM1 promotes proteasomal degradation of FLNA and RAD51 within the nucleus, resulting in reduced levels of nuclear RAD51 and slower DNA repair. SQSTM1 regulates the ratio between HR and nonhomologous end joining (NHEJ) by promoting the latter at the expense of the former. This SQSTM1-dependent mechanism mediates the effect of macroautophagy on DNA repair. Moreover, nuclear localization of SQSTM1 and its association with DDF increase with aging and are prevented by life-span-extending dietary restriction, suggesting that an imbalance in the mechanism identified here may contribute to aging and age-related diseases.